Investigation of antioxidant properties and influence on activity of collagenase and elastase of selected raw herbal materials from traditional Eastern medicine - Julia Lewandowska; Maria Zych; Katarzyna Szałabska-Rąpała; Ilona Kaczmarczyk-Żebrowska (Śląski Uniwersytet Medyczny w Katowicach, 2024)
Introduction: Traditional Eastern medicine (TEM) is becoming increasingly more popular in highly developed Western countries as an alternative form of supporting health and body care. Many herbs used in this medical practice possess antioxidant, anti-inflammatory and immunomodulatory effects. The skin aging process may progress with age, when collagen and elastin fibers gradually decrease. Excessive exposure to UV radiation, resulting in an increase in the production of free radicals, leads to damage at the molecular level to numerous structures in the body including the acceleration of skin aging. Material and methods: The content of polyphenolic compounds (among others: phenolic acids and flavonoids), antioxidant potential (ABTS, DPPH and FRAP assays) as well as the influence on the activity of enzymes, collagenase and elastase, were determined in infusions obtained from Gynostemma pentaphyllum, Tinospora cordifolia, Astragalus membranaceus, Codonopsis pilosula, Asparagus racemosus and Ocimum sanctum. Results: The highest content of polyphenolic compounds and the strongest antioxidant properties were observed in the infusions obtained from the O. sanctum herb, while the greatest ability to inhibit collagenase and elastase was observed in the infusions obtained from the T. cordifolia leaves. Conclusions: Infusions from the O. sanctum herb and T. cordifolia leaves may have a potentially beneficial effect on the skin and may be used in anti-aging formulations.